2013
DOI: 10.1111/puar.12046
|View full text |Cite
|
Sign up to set email alerts
|

Does Deployment to War Affect Public Service Motivation? A Panel Study of Soldiers Before and After Their Service in Afghanistan

Abstract: Exposure to the extreme stress of warfare may affect soldiers’ perceptions of others and society. Using panel data from two companies on a tour of duty to Afghanistan in 2011, this article analyzes how different dimensions of soldiers’ public service motivation are influenced by deployment to war. As expected, soldiers’ compassion decreased and commitment to the public interest increased, while self‐sacrifice did not change systematically. Deployment to war was expected to affect inexperienced soldiers more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 36 publications
4
56
0
1
Order By: Relevance
“…Arguably, affective PSM motives that are strongly rooted in core personality traits can be expected to be stable over time, and change only as a result of exposure to extreme events. This is in line with the findings of Braender and Andersen (2013), who showed that soldiers returning from a military campaign in…”
Section: Resultssupporting
confidence: 80%
“…Arguably, affective PSM motives that are strongly rooted in core personality traits can be expected to be stable over time, and change only as a result of exposure to extreme events. This is in line with the findings of Braender and Andersen (2013), who showed that soldiers returning from a military campaign in…”
Section: Resultssupporting
confidence: 80%
“…Table shows some of the diverse PSM concepts one finds in the literature. In some cases, authors equate PSM with general altruistic motive (e.g., Brænder and Andersen ; Brewer, Ritz, and Vandenabeele ; Bright ; Francois ; Houston ; Pandey, Wright, and Moynihan ; Perry and Hondeghem , ; Rainey and Steinbauer 1999; Wright and Pandey ), work‐related preferences (e.g., Brewer, Ritz, and Vandenabeele ; Christensen and Wright ; Clerkin and Coggburn ; Georgellis and Tabvuma ; Kjeldsen , 2012c; Liu, Tang, and Zhu ; Perry and Hondeghem ), or prosocial behaviors (e.g., Andersen et al ; Brænder and Andersen ; Brewer, Ritz, and Vandenabeele ; Christensen and Wright ; Clerkin, Paynter, and Taylor, ; Perry and Hondeghem ). Some conceptualizations focus on individual predisposition (Carpenter, Doverspike, and Miguel ; Clerkin and Coggburn ; Crewson ; Pandey, Wright, and Moynihan ; Perry et al ; Perry and Wise ), while others pay attention to institutional and ethical factors in shaping PSM (Coursey et al ; Houston ; Houston and Cartwright ; Perry and Hondeghem ).…”
Section: Public Service Motivation Conceptualization: Some Notes For mentioning
confidence: 99%
“…Gradually, the concept of public service motivation has moved outside these narrow confines. Although the concept is still being applied to the civil service (Kim et al ), empirical research has identified public service motivation with those who deliver public service, regardless of the locus of employment, including fire‐fighters, police officers, nurses, social workers, teachers, military personnel, and even volunteers (Perry et al ; Andersen et al ; Kim ; Bellé ; Braender and Andersen ; Van Loon et al ; Kjeldsen ).…”
Section: What Knowledge Has Been Generated So Far?mentioning
confidence: 99%